Self-employment strategies: Transforming job loss into entrepreneurial success in the post-pandemic gig economy - Syahrul Nizam Salam; Jasman Bandar; Suddin Lada; Abdul Said Ambotang; Ghazali Sulaiman; Mazni Muhammad (Human Resource Management Academic Research Society (HRMARS), 2024)
The study investigates the broad impact of the pandemic on health, social dynamics, and the economy, particularly resulting in widespread job losses. It aims to understand how individuals, facing unemployment due to layoffs, downsizing, or health-related resignations, strive for economic independence post-pandemic. Utilizing a descriptive design with a qualitative approach, the research employs Maslow's theoretical framework to explain the journey towards independence. Findings reveal pervasive negative effects on the economy and individuals' lives. Notably, the pandemic instigates motivation, leading individuals to explore diverse job opportunities, and enhancing economic stability for survival. The study proposes a practical solution, advocating for self-employment in the form of "Gig Economy" entrepreneurship. This contributes scientifically and offers a guide for both researchers and the local community navigating post-pandemic challenges.